Expanding norm theory in TIS: Proposal for a framework of translator norms - Strowe, Anna (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2024)
This article is comprised of a rationale and proposal for a framework of “translator norms,” intended to extend and complement the existing norm frameworks in Translation Studies. The proposed concept of translator norms focuses on normative behaviors and expectations around the figures of translators as individuals, rather than on the process and product aspects that have predominantly been the focus of existing work on translation norms. Translator norms, as described here, tend to logically precede the work of translation and often relate to the hiring and selection of translators. The categories proposed are discussed with reference to existing scholarship in Translation and Interpreting Studies that highlights the kinds of tendencies and values that can be interpreted in terms of norms. While the norms themselves are not the focus of the article, some specific norms are discussed in the elaboration of the categories within which we might investigate them and others. Retheorizing these areas as part of a structure of translator norms can help promote critical evaluation of assumptions and implications of particular decisions around translators that may turn out to be context-specific and normative rather than universal. A re-evaluation of some of these assumptions can in turn facilitate decolonizing approaches in translation and Translation Studies by calling attention to previously devalued practices, identities, and forms of knowledge.